Service innovations for people with multiple long-term conditions: reflections of a rapid evaluation team - Jon Sussex; Judith Smith; Frances M Wu (NIHR Journals Library, 2024)
Background People living with multiple long-term conditions represent a significant concern for National Health Service policy and practice, and their care is a major theme in the 2019 National Health Service Long Term Plan. The Birmingham RAND and Cambridge Rapid Evaluation Centre team has undertaken a thematic synthesis of the 10 evaluations it has conducted from 2018 to 2023, exploring the needs, priorities and implications for people with multiple long-term conditions. Objectives The aims for this overarching study were to: (1) build a body of learning about service innovations in primary and community settings for people of all ages with multiple long-term conditions, focused on questions that matter most to people with multimorbidity; and (2) develop methodological insights about how rapid evaluation can be used to inform the scoping, testing and implementation of service innovations for people with multiple long-term conditions. Design The focus on multiple long-term conditions came from a Birmingham RAND and Cambridge Rapid Evaluation Centre prioritisation process undertaken in 2018 using James Lind Alliance methods. Cross-analysis of the findings from the 10 individual rapid evaluations was supplemented by (1) building aspects of multimorbidity into the design of later evaluations; (2) interviewing national and regional stakeholders (n=19) working in or alongside integrated care systems; (3) undertaking a rapid review of evidence on remote monitoring for people with multiple long-term conditions (19 papers included); and (4) testing overall insights with organisations representing patients and carers through a patient, public and professional engagement workshop with 10 participants plus members of the research team. Results While living with multiple long-term conditions is common and is the norm for people over the age of 50 using health and care services, it is not often a focus of health service provision or innovation, nor of research and evaluation activity. We discuss six themes emerging from the totality of the study: (1) our health system is mainly organised around single conditions and not multiple long-term conditions; (2) research calls and studies usually focus on single conditions and associated services; (3) building opportunities for engaged, informed individuals and carers and improved self-management; (4) the importance of measures that matter for patients and carers; (5) barriers to developing and implementing service innovations for people with multiple long-term conditions; and (6) what is needed to make patients with multiple long-term conditions a priority in healthcare planning and delivery. Limitations Care of people with multiple long-term conditions was not the principal focus of several of the rapid evaluations. While this was a finding in itself, it limited our learning about designing and implementing, as well as methodological approaches to evaluating, service innovations for people with multiple long-term conditions. Conclusions Through a thematic analysis of the portfolio of evaluations, we have deduced a set of suggested implications for how the needs of people with multiple long-term conditions can be better embedded in policy, research and practice. Future work Areas of uncertainty related to the care of people with multiple long-term conditions should be further explored, including developing and testing measures of patient experience of (un)co-ordinated care across settings, and interrogating the experience of health and care staff when working with people with multiple long-term conditions, to understand what works. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR134284) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 15. See the NIHR Funding and Awards website for further award information. Plain language summary Many people in England live with two or more physical and/or mental health conditions that are expected to last for years. Estimates vary, but it is likely that a majority of National Health Service services are serving people living with two or more long-term conditions. We wanted to find out how well the needs of this group are taken into account when new types of health care are introduced, or existing services are reorganised. To do this, we went back to all 10 of the health service innovations that had been studied by our Birmingham RAND and Cambridge Evaluation Centre from 2018 to 2023. We did some extra research, including discussions with patient representatives and interviews with National Health Service policy-makers and managers at national and regional levels. We also looked at what new research had been published about one example of a new healthcare technology that is intended to help people who have several long-term health conditions: monitors that can be used by health service staff to measure patients' symptoms when they are in their own home. Our main finding was that most National Health Service attention is given to organising care for single conditions, often treating them in isolation. Patients' many treatments and needs are not routinely considered all at the same time by healthcare staff, nor by researchers. Care for one condition is too often not co-ordinated with care for other health problems that a patient may have. Although the situation of people living with several long-term health conditions is in principle understood by healthcare staff, managers and researchers, relatively little is done in practice to meet their needs. We conclude by suggesting ways that policy-makers, healthcare staff and researchers could improve how they help people living with multiple long-term conditions.